Potential Ornamental Plants and their Contribution to the Domestic Gardens and Landscape - Joseph, Delna; Thomas, Binu; Arumugam, Rajendran (Research in Plant Biology, 2013)
The present study identified 146 species belonging to 129 genera in 63 families withpotential pretty ornamental value from Gudalur Taluk of Nilgiri district, Tamil Nadu. Theresults indicated that Gudalur Taluk of Nilgiri district had abundance of wild ornamentalplants which exhibits wide range of diversity in terms of taxa, habit and growth forms.